Potential paraneoplastic syndromes and selected autoimmune conditions in patients with non-small cell lung cancer and small cell lung cancer: A population-based cohort study - Miret, Montserrat (PLoS One, 2017)
BACKGROUND: Little is known about the occurrence and distribution of types of paraneoplastic syndromes (PNS) in patients with lung cancer. Identification of autoimmune PNS is particularly important for discerning them from immune-related adverse events of novel immunotherapies. We estimated the occurrence of PNS among patients with lung cancer and compared it with that in the general population. METHODS: In this registry-based cohort study in Denmark, we identified all patients with incident primary lung cancer between 1997 and 2010, and in a general-population comparison cohort matched on calendar time, sex, age, and residence. Among patients with non-small cell lung cancer (NSCLC) and small-cell lung cancer (SCLC), we estimated prevalence of potential PNS and selected autoimmune conditions and compared their incidence rates with those of equivalent conditions in the general population cohort, using hazard ratios (HRs) adjusted for baseline comorbidity. RESULTS: There were 35,319 patients with NSCLC and 6,711 patients with SCLC. The incidence rates per 1000 person-years (95% confidence interval) of any potential PNS or selected autoimmune disorders were 135.4 (131.9–139.1) among NSCLC patients and 237.3 (224.4–250.5) among SCLC patients. Adjusted HRs for any potential PNS or selected autoimmune disorders were 4.8 (4.7–5.0) for NSCLC and 8.2 (7.6–8.8) for SCLC. CONCLUSION: Incidence rate of any potential PNS or selected autoimmune disorders among patients with lung cancer was greater than that in the general population and was greater after SCLC than after NSCLC. IMPACT: These results provide context to discerning PNS from adverse effects of novel immunotherapies during the clinical course of NSCLC and SCLC.